2010
DOI: 10.1016/j.vaccine.2009.12.033
|View full text |Cite
|
Sign up to set email alerts
|

A summer school on vaccinology: Responding to identified gaps in pre-service immunisation training of future health care workers

Abstract: A summer school on vaccinology: Responding to identified gaps in pre-service immunisation training of future health care workers a r t i c l e i n f o Immunisation is one of the corner stones of public health. Most health care consumers see the health care worker as their major source of information on immunisation and vaccine safety. Doctors, nurses and midwives should be appropriately and timely trained for that role. Within the Vaccine Safety, Attitudes, Training and Communication (VACSATC) EU-project a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 20 publications
(30 reference statements)
1
33
0
2
Order By: Relevance
“…This finding is consistent with previous published studies that reported low levels of vaccine safety education during medical training in Europe and Canada [20,46] and an unpublished, cross-sectional survey of 452 GPs, GP nurses, midwives, paediatric and community nurses, conducted in Sydney, Australia [47]. Our study confirms a need to provide adequate education across healthcare providers’ training, both pre- and in-service, which has been recognised internationally [46,48]. Adverse event reporting should be incorporated in continuing medical education programs.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous published studies that reported low levels of vaccine safety education during medical training in Europe and Canada [20,46] and an unpublished, cross-sectional survey of 452 GPs, GP nurses, midwives, paediatric and community nurses, conducted in Sydney, Australia [47]. Our study confirms a need to provide adequate education across healthcare providers’ training, both pre- and in-service, which has been recognised internationally [46,48]. Adverse event reporting should be incorporated in continuing medical education programs.…”
Section: Discussionsupporting
confidence: 94%
“…58,61 Studies have shown, however, that HCPs' knowledge about vaccination issues is variable and that training in vaccinology is poor or non-existent in medical curricula in many countries. 62 In a French hospital study, only 25% of HCPs were able to list correctly the three mandatory vaccines. 63 Similarly, only 12.9% of Greek HCPs correctly named the vaccines recommended for them by the Ministry of Health.…”
Section: Hcp Involvementmentioning
confidence: 99%
“…One proven approach is to develop midcareer training opportunities. [3][4][5] Scale up can occur using coalitions of teaching sites. 6…”
Section: Introductionmentioning
confidence: 99%